IMMEDIATE APPLY COST-EFFECTIVE EASILY PREPARABLE-AVAILABLE 21STCENTURY POTENTIAL-AYURVEDIC-HERBAL-INTEGRATIVE-MEDICINAL-VACCINE OF COVID-19: ACHIEVED AGRICULTURE HEALTHCARE-SOCIO-ECONOMY SCIENCE TECHNOLOGY COMMUNICATION MECHANISM! - Datta, Subhas Chandra (International Journal of Research -GRANTHAALAYAH, 2021)
The 5th epidemic-COVID-19 spreads all around the world forming total change of the world health, education, research, travel, socioeconomic, and human civilization, and the proper potential vaccine still unknown for the future efficacy of reinfection outbreaks of the vaccinated peoples with manufacturing capacity for the whole world population including new variant also. The poor marginalized society, aged people, street -children, and -animals, are not able to manage and purchase vaccines. And the pandemic must be controlled or managed by every nation; otherwise, a globe is at risk of further outbreaks, and India with the whole world develop a policy to overcome the pandemic-COVID-19. India emphasis on consumption of vegetable as the preventive traditional-ayurvedic-medicines against many naturally-infected-diseases of man, animals and plants caused by various-pathogens, remarkably reducing agricultural productions. The various-pesticides reduce the plant-diseases, but it is not cost-effective and environment-friendly. The present treatment confirms the flowering-meristems of wormwoods-Artemisia nilagirica (Clarke) Pamp, prepared or developed the ayurvedic-medicine, dissolved in germfree-tap-water applying foliar-spray against plant-diseases, and the molecular-weight of soluble-root-proteins were determined. The recent treatment confirms once again that the ayurvedic-medicines-prepared from the flowering-meristems of Artemisia nilagirica (Clarke) Pamp are very much effective in controlling different-plant-pathogens caused many-diseases, synthesizing many new PR-proteins (pathogenesis-related-protein), boosting their response of defense naturally against pathogens, and increased growth of plants and protein-content, by confirming the “Immediate Apply Cost-Effective Easily Preparable-Available 21stCentury Potential-Ayurvedic-Herbal-Integrative-Medicinal-Vaccine of COVID-19: Achieved Agriculture Healthcare-Socio-Economy Science Technology Communication Mechanism with Clinical, Physical, Chemical, Biological, Physiological, and Molecular Weight”, by boosting-immunity. And it will be best side-effect-free potential-ayurvedic-COVID-19-Vaccine due to an ultra-diluted-low-dose, and globally develop all aspects in the scientific-basis of the ayurvedic-biomedicines, and it is thought that the present problems of the civilization of human will soon be overcome as early as possible retaining whole world in the new-normal or old-forms against the COVID-19.